Estudo histológico e histoquímico de próstata de cães em diferentes idades - Carolina Vilaca Santana (2006)
The current work aimed at characterising secretions of canine prostates at different ages by means of Histochemistry. Sixty-seven canine prostates divided into three age groups have been studied: the first including young animals with ages between two months and 2.5 years old, the second with adult animals whose ages varied from three to six years old, and the third group with old animals with ages varying from seven to seventeen years old. Prostatic alterations have been noticed in all the three groups: 12 prostates had BPH (Benign Prostate Hyperplasia), 10 had prostatitis, and 30 animals had BPH associated to prostatitis. Histochemically, a bigger intensity of neutral and nonsulfated acid mucosubstances secretion has been noticed in the adult and old groups, respectively. The intensity of sulfated acid mucosubstances was more noticeable in the adult group with statistically significant decrease in the old group. The production of proteins rich in NH2 radicals was higher in the adult group. Therefore, one may conclude that the prostrate produces neutral carboxilated acid mucosubstances with more intensity in the old group and acid nonsulfated ones in the adult group. There is a correlation between the increase of secretion intensity of neutral mucosubstances and those mucosubstances with NH2 radicals in the adult and old groups and an increase of the BPH-prostatitis Complex in the related groups.